Research and application on data security sharing technology platform for oil and gas pipeline network based on privacy computing - REN Wu; ZHANG Ke; FU Yingjie; ZHANG Zhengxiong; CAI Yongjun (大数据)
To effectively ensure the security of key information and data resources in the oil and gas pipeline network, and further unleash the value of data, research and application of a privacy computing based oil and gas pipeline network data security sharing technology platform are conducted. Firstly, analyze the current situation of data security sharing in oil and gas pipeline networks from three aspects: policy, technology, and industry, and expose the contradiction between data security compliance and data sharing needs. Then, design and implement a data security sharing platform for oil and gas pipeline networks to address this issue, and provide detailed descriptions of three key algorithm principles, achieving "original data not out of domain, usable but invisible" and "controllable and measurable". Afterwards, thedata security sharing scenarios for the oil and gas pipeline network industry will be sorted out, and data security sharing technology will be applied in combination with three typical application scenarios. The results indicate that the data security sharing technology platform for oil and gas pipeline networks based on privacy computing effectively realizes internal data exchange and external data sharing of oil and gas pipeline network enterprises, breaks down barriers between data, ensures secure sharing and circulation of data between various business chains, and improves the level of oil and gas pipeline network management and control.